Identification of an activator protein required for the induction of fruA, a gene essential for fruiting body development in Myxococcus xanthus - Ueki, Toshiyuki (National Academy of Sciences, 2003)
Myxococcus xanthus exhibits social behavior and multicellular development. FruA is an essential transcription factor for fruiting body development in M. xanthus. In the present study, the upstream promoter region was found to be necessary for the induction of fruA expression during development. A cis-acting element required for the induction was identified and was located between nucleotides –154 and –107 with respect to the transcription initiation site. In addition, it was found that two binding sites exist within this element of the fruA promoter. By using DNA affinity column chromatography containing the cis-acting element, a fruA promoter-binding protein was purified. The purified protein was shown by N-terminal sequence analysis to be identical to MrpC, a protein identified previously by transposon insertion mutagenesis as an essential locus for fruiting body development [Sun, H. & Shi, W. (2001) J. Bacteriol. 183, 4786–4795]. Furthermore, fruA mRNA was not detectable in the mrpC::km strain, demonstrating that MrpC is essential for fruA expression. Moreover, mutational analysis of the binding sites for MrpC in the fruA promoter indicates that binding of MrpC activates transcription of fruA in vivo. This report provides evidence for a direct molecular interaction involved in temporally regulated gene expression in M. xanthus.